PENGARUH KUALITAS LAYANAN, KEPUASAN, KEPERCAYAAN DAN KOMITMEN TERHADAP MINAT BERKUNJUNG KEMBALI PADA INDUSTRI KECANTIKAN - Berlianto, Margaretha Pink (Journal of Management and Business Review, 2018)
This study aims to analyze the effect of service quality on satisfaction, and the relationship of satisfaction, trust, and commitment to the revisit intention in the salon industry. There are five hypotheses tested in this study. The samples size that feasible and can be used are 185, by distributing questionnaires to salon customers’ X in Jakarta. Data analysis method in this study used PLS-SEM. The sampling technique used purposive sampling method. The results of this study are service quality has a positive effect on satisfaction, satisfaction has a positive effect on trust and revisit intention, trust has a positive commitment, and commitment has a positive effect on revisit intention. The implications of this research are salon business owner or manager need to pay attention to various aspects, such as using an up to date equipment, employee appearance, salon room have a good visually appealing, reliable, has good responsiveness, guarantees good transactions, a good product knowledge, employees are polite and have empathy. They also have to create satisfaction, trust, and commitment of their customers to encourage revisit intention.